Efeito "bubble up” - do oriente para o ocidente: a influência do street style do Japão na concepção de uma marca para "otakus" ou "otomes" no Brasil - Carmo, Bárbara Correa do (2015)
This research it is a study of the effect "Bubble Up" – also known as effect "Bubbles" – consisting of the trends that come from the streets and end up being used on the runways in collections of renowned designers. The approach is focused on identifying this effect through fashion Street Style present in the streets of Japan and how trends "Bubble Up" from the East can be inserted to design garments for Western countries. Thus, a specific group circulating in the streets of Japan – known as "Decora" – as the parameter for identifying aesthetic-symbolic elements approaching the longings consumption of another existing group in Brazil, known as "otakus" or "otomes" – who are young appreciative of female japanese pop culture, specifically manga fans and anime (japanese comics and cartoons). The proposal to develop this brand targeted to that audience in Brazil came from the growing phenomenon of women who want to express their identity through costumes that contextualize the joyful universe and relaxed characteristic of the characters of manga and anime, but at the same time does not constitute mere fantasies only used in "cosplay" events, but in garments that can be used in common public places and in various day-to-day.